Intercropping tea plants with different leguminous green manures enhances soil nutrient availability, thereby reshaping the structure and functional potential of soil microbial communities - Liu, Qin; Wang, Li-xian; Chang, Pei-yu; Zhang, Jian-gen; Li, Chen; Shuang, Qiao-yun; Zhang, Chun-yun; Lu, Zhi-Kai; Wang, Xiao-ling; Jiang, Xin-feng (Frontiers in Microbiology, 2026)
Long-term monoculture in tea plantations leads to soil fertility decline and microbial community degradation, restricting tea growth and ecosystem function. To explore sustainable management strategies, we conducted a field experiment in a 40-year-old Camellia sinensis cv. “Fuding Dabai” plantation with intercropping of three leguminous green manures: alfalfa (TAL), hairy vetch (THV), and Chinese milk vetch (TMV). All treatments significantly improved bud density, hundred-bud weight, and yield, with TAL and THV increasing spring and summer yields by more than 40% and THV achieving the highest autumn yield (650.17 kg·hm−2). Soil fertility was markedly enhanced, particularly under THV, with notable increases in organic matter, nitrogen, and available phosphorus. Enzyme activities responded differentially: TAL enhanced urease and sucrase, TMV promoted amylase and phosphatase, and THV increased catalase activity. High-throughput sequencing revealed shifts in bacterial (Pseudomonadota, Planctomycetota) and fungal (Ascomycota, Basidiomycota) communities, with THV showing the highest bacterial OTU richness. Functional predictions indicated enhanced microbial potential in carbon, nitrogen, and phosphorus cycling, especially under THV. Overall, leguminous green manure intercropping improved soil fertility, enzyme activity, and microbial communities, thereby enhancing tea yield, with hairy vetch showing the most consistent benefits. These findings provide insights into microbial-mediated soil improvement and offer a sustainable pathway for managing aging tea plantations.